Investigation of Lithologic Discontinuities Phenomenon in Andisols derived from Mt. Patuha - Devnita, Rina; Arifin, Mahfud; Sandrawati, Apong (Soilrens, 2024)
Lithologic discontinuity reflects the distinct change between different types of soil layers that can occur due to various geological process, resulted in variation composition, colour, texture, organic matter, consistency, structure, and others characteristics. Soils derived from volcanic eruption have the possibility to have lithologic discontinuity in the depth of the soil profiles due to the different eruption that formed the soils. Soils developed from the eruption of Mt. Patuha were investigated whether lithologic discontinuity presence the soil layers. The research used descriptive and comparative method of two profiles, analysed the soil macro-morphology and soil laboratory analyses covered colour, organic carbon, texture, consistency and structure. The result showed that the unusual pattern distributed of colour, organic matter, consistency, structure indicated the lithologic discontinuities of the underlying 2Ab (A buried) horizon to the overlying horizon. The darker colour, higher organic matter content, friable consistency in 2Ab in deeper depth, were some indications of lithologic discontinuities, where in soil without lithologic discontinuities the deeper depth or horizon was normally lighter colour, lower organic matter content and firmer consistency. However, detailed analysed with instruments like XRF and VIS DRS are needed to have the precise elemental composition in every horizon which conclude the horizon from the same or different parent materials.